2018
DOI: 10.1103/physrevc.98.014318
|View full text |Cite
|
Sign up to set email alerts
|

ΛΛ pairing in multistrange hypernuclei

Abstract: Multi-strange Ca, Sn and Pb hypernuclei with ΛΛ pairing interaction are investigated within the Hartree-Fock-Bogoliubov approach. The unknown ΛΛ pairing strength is calibrated to match with the maximal value for the prediction of the Λ pairing gap in uniform matter for densities and isospin asymmetries equivalent to those existing in multi-Λ hypernuclei. In this way, we provide an upper bound for the prediction of the Λ pairing gap and its effects in hypernuclei. The condensation energy is predicted to be abou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
3
12
1
Order By: Relevance
“…Finally, astronomical observations and terrestrial experiments can be translated to microscopic constraints through the symmetry energy [265], the energy budget for increasing asymmetry between neutrons and protons. Various studies have empirically identified correlations between various combinations of parameters that characterize the symmetry energy and its density dependence with the neutron star radius and tidal parameters [246,[266][267][268][269] or terrestrial experimental results [239,[270][271][272], as they all are linked to the low-density behavior of the equation of state around (twice) saturation. The tidal constraints from GW170817, and more recently radius constraints from NICER have been used to examine implications for the symmetry energy [273][274][275][276][277][278][279][280][281][282] as well as potential systematics in the mapping [283].…”
Section: Microscopic Propertiesmentioning
confidence: 99%
“…Finally, astronomical observations and terrestrial experiments can be translated to microscopic constraints through the symmetry energy [265], the energy budget for increasing asymmetry between neutrons and protons. Various studies have empirically identified correlations between various combinations of parameters that characterize the symmetry energy and its density dependence with the neutron star radius and tidal parameters [246,[266][267][268][269] or terrestrial experimental results [239,[270][271][272], as they all are linked to the low-density behavior of the equation of state around (twice) saturation. The tidal constraints from GW170817, and more recently radius constraints from NICER have been used to examine implications for the symmetry energy [273][274][275][276][277][278][279][280][281][282] as well as potential systematics in the mapping [283].…”
Section: Microscopic Propertiesmentioning
confidence: 99%
“…The density functional, deduced from the G-matrix calculation in uniform matter, will be generically named as DF-NSC89, DF-NSC97a and DF-NSC97f, hereafter, see Ref. [31] for more details. The oldest DF-NSC89 functional can reproduce with a good accuracy the experimental single particle energies of Λ hyperon for light hypernuclei such as 5 Λ He or 13 Λ C, but for the heavier hypernuclei like 41 Λ Ca or 209 Λ Pb, DF-NSC97a and DF-NSC97f give results close to the experimental data [30,32].…”
Section: Introductionmentioning
confidence: 99%
“…So far there is only one confirmed double-Λ hypernucleus 6 ΛΛ He [10] and two candidates 13 ΛΛ B [11] and 10 ΛΛ Be [12]. Nevertheless, many theoretical efforts have been devoted to investigating the structure of more double-Λ and even multistrangeness (−S ≥ 3) hypernuclei [13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…Since the pairing strength for Λs has been taken as 4/9 of that for nucleons, it is not unexpected that the pairing effects of Λs are weaker compared to nucleons. [19] with SLy5 for the NN interaction and DF-NSC89, DF-NSC97a and DF-NSC97f for the ΛN interaction in the ph channel. In the MDC-RHB calculations, the effective interactions PK1-Y1 and NLSH-A are used for the ph channel and the separable pairing force of finite range with the pairing strength G Λ = 4/9 • G N = 323.56 MeV•fm 3 is used for pp channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation